Supervisi Pendidikan Agama Islam di Lembaga Sekolah Tingkat Dasar - Rizal Ariansyah, M (AL MURABBI, 2024)
Islamic education supervision is tasked with carrying out operations and supervising Islamic education in both school institutions and madrasas. The aim of implementing supervision of Islamic religious education in schools/madrasas in supervision of Islamic education is carried out by implementing it in providing services and coaching to deepen teacher performance so that they work professionally in carrying out their duties in schools/madrasas to achieve educational goals effectively and efficiently. The research methodology uses a qualitative approach by understanding a phenomenon that has occurred, carried out by collecting descriptive data and analyzing it qualitatively. Data collection was done by observation and literature study. The data collected was analyzed qualitatively by identifying themes that emerged from the data. The identified themes will be used to evaluate the development of Islamic religious education teachers in school/madrasah institutions. The results of this research related to supervision are to obtain changes so that the efforts made by supervisors in guiding and guiding teachers to work professionally regarding the teaching and learning process in front of the class in schools/madrasahs can be carried out well in accordance with provisions that have been regulated. If teacher training is carried out well, it is hoped that it can develop enthusiasm for the performance of teachers in carrying out their duties and also have a sense of responsibility for the tasks they carry out.